Pengaruh Atraksi Wisata, Citra Destinasi dan Aksesibilitas, Terhadap Minat Berkunjung Wisatawan di Objek Wisata Gunung Dago, Bogor - Triandi Pradana; Antony Stefanus Purba (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Dago Mountain is located in Dago Village, Cikuda Wanaherang, Parung Panjang, Bogor, West Java. This tourist attractions is arguably still quite new in the city of Bogor, because it was launch around 2019. The natural tourism area of Mount Dago is located on land that responsible to PT. Perhutani. Then it was handed over to the residents to be managed through “Lembaga Masyarakat Desa dan Hutan” (LMDH). This study aims to find out how the influence of attraction, destination image and accessibility influences the interest in visiting tourists with a total of 90 respondents. The analysis in this study uses the Multiple Linear Regression method and it is obtained that partially the Attraction variable has a significant effect on Interest in attending as evidenced by the Sig value. 0.225 > 0.05 and t count 2.964 <t table 1.987. The same results were obtained for the Destination Image variable which partially had a significant effect on present interest as evidenced by the Sig.0.07 value > 0.05 and the t-count value of 2.996 <t-table 1.987. Then the Accessibility variable shows a significant influence on Interest in Visiting, as evidenced by the value of Sig.0.05 = 0.05 and the t-count value of 6.376 <t-table 1.987